Guidelines for photography of cutaneous marks and injuries: a multi-professional perspective. (May 2014) - Evans, Sam; Baylis, Sonya; Carabott, Romina; Jones, Michael; Kelson, Zoe; Marsh, Nick; Payne-James, Jason; Ramadani, Jona; Vanezis, Peter; Kemp, Alison
Abstract Investigators assessing the likelihood of physical abuse, must make a decision as to whether the injury seen matches the explanation given. In some instances the pattern of these injuries can give the investigator a possible link to the cause of the injury. Thus, matching an injury pattern to an implement or weapon used has forensic implications. The current method of capturing patterned injuries together with poor scale placement often result in some form of distortion that causes a change to the shape of the patterned injury. The aim of this guideline is to assist individuals dealing with the capture of photographic evidence for the investigation of suspected non-accidental patterned cutaneous injuries (PCI), and to ensure high standards of image quality are met for both evidential records and for forensic analysis. The technical equipment specified within these guidelines are recommended by the authors as a basic requirement for imaging best practice, due to their ability to capture detailed and critical data. For precise pattern matching analysis, it is vital that both the injury and the suspected implement are photographed in accordance with this guidance.